ower line corridors in pine forests as habitats for ground beetles (Coleoptera, Carabidae) in the Belarusian Poozerie - Anatoly A., Lakotko; Gennadi G., Sushko (Journal of the Belarusian State University. Ecology, 2021)
For the first time in the Belarusian Lake District, the influence of regular tree felling in pine forests under power lines on the biodiversity of ground beetles has been studied. On the power line corridor species richness, number of individuals, and the diversity of ground beetles were highest in comparison with the adjacent forests (Pinetum vacciniosum and Pinetum myrtillosum). In addition, species composition and group of dominants composition were different. Among dominant species there are inhabitants of open spaces Poecilus versicolor and Calathus erratus. The assemblages of ground beetles of the power line corridor were the most differed from Pinetum vacciniosum. Regression analysis (GLM) showed a negative influence of the height of the herb-dwarf shrub layer on the number of individuals of ground beetles. Shrub cover positive affected carabid diversity, whereas soil moisture had a negative effect.